Queen's Park Hotel, Port of Spain, Trinidad. - (:unkn) unknown (My University, 2010)
Photo of the Queen's Park Hotel in Port of Spain, Trinidad and Tobago. Hand-written letter. One penny Trinidad stamp.
Colour: White and Grey Hues; Style: Landscape; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; 1901; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Fences--Trinidad and Tobago; Fretwork; Queen's Park Savannah (Port of Spain)